2007
DOI: 10.1111/j.1540-4560.2007.00507.x
|View full text |Cite
|
Sign up to set email alerts
|

The Emotional Climate of Nations and Their Culture of Peace

Abstract: Societies seem to have emotional climates that affect how people feel and act in public situations. Unlike the emotions experienced in an individual's personal life, these modal feelings reflect a collective response to the socio-economic-political situation of the society and influence how most people behave toward one another and their government. A government may foster a climate of fear to ensure social control, or it may encourage the formation of heterogeneous social groups to facilitate a climate of tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 28 publications
0
31
0
4
Order By: Relevance
“…Perceived socioemotional climate in participants' country following the terrorist attack was assessed with a set of eight items extracted and adapted to the post-terrorist context from two different instruments: The Emotional Climate Scale (Páez et al, 1997) and The Climate Dimension Scale (de Rivera, 1992;de Rivera et al, 2007). Participants were asked to assess their agreement with statements related to the positive socioemotional climate (i.e., people's institutional trust, manifestation of confidence and cooperation between the various social groups, manifestation of solidarity and mutual helping between people and people's hope about the future) and to the negative socioemotional climate (i.e., feeling insecure because of the amount of recent violence, being afraid of saying of what people really think, feeling of anger and hostility, being afraid and despaired).…”
Section: Socioemotional Climate Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceived socioemotional climate in participants' country following the terrorist attack was assessed with a set of eight items extracted and adapted to the post-terrorist context from two different instruments: The Emotional Climate Scale (Páez et al, 1997) and The Climate Dimension Scale (de Rivera, 1992;de Rivera et al, 2007). Participants were asked to assess their agreement with statements related to the positive socioemotional climate (i.e., people's institutional trust, manifestation of confidence and cooperation between the various social groups, manifestation of solidarity and mutual helping between people and people's hope about the future) and to the negative socioemotional climate (i.e., feeling insecure because of the amount of recent violence, being afraid of saying of what people really think, feeling of anger and hostility, being afraid and despaired).…”
Section: Socioemotional Climate Assessmentmentioning
confidence: 99%
“…According to the conclusions drawn from the theoretical review of Drozda-Senkowska and Oberlé (2006), the social climate refers to a metaphor-concept related to circumstances in which we are living. Similarly, the emotional climate has been defined as a set of feelings reflecting collective responses to the general situation of the society, including the social, political and economic structures of the society (de Rivera, 1992;de Rivera, Kurrien, & Olsen, 2007). Contrary to personal emotions which refer to strictly personal feelings of individuals, the socioemotional climate refers to a macro-social phenomenon including emotions and social situations perceived by the citizens within a concrete society (Conejero & Etxebarria, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, research suggests that such normative influences can create widely accepted systems of dysfunctional behavior, shape employee perceptions of normality, and promote a variety of negative organizational and employee outcomes (Balthazard et al, 2006;Van Fleet and Griffin, 2006). In fact, several authors have suggested that organizational climates can serve as social control systems based on shared norms (de Rivera et al, 2007;O'Reilly and Chatman, 1996).…”
Section: Perceptions Of Aversive Leadershipmentioning
confidence: 99%
“…Además de lo anterior, investigaciones en contextos post violencia política refieren al clima emocional como una variable necesaria a explorar (Cárdenas, Páez, Rimé, Bilbao & Asún, 2014;de Rivera, Kurrien & Olsen, 2007;de Rivera & Páez, 2007;Techio et al 2011). El clima emocional se define como el conjunto de emociones percibidas como predominantes colectivamente, que son independientes de la emocionalidad personal y que emergen de la interacción social en determinados contextos y momentos históricos (de Rivera et al, 2007;de Rivera & Páez, 2007).…”
Section: Bienestar Valores Y Clima Emocionalunclassified
“…El clima emocional se define como el conjunto de emociones percibidas como predominantes colectivamente, que son independientes de la emocionalidad personal y que emergen de la interacción social en determinados contextos y momentos históricos (de Rivera et al, 2007;de Rivera & Páez, 2007). La predominancia de ciertas emociones colectivas funcionaría como un factor de influencia en la manera en que se desarrollan las relaciones interpersonales en el endogrupo .…”
Section: Bienestar Valores Y Clima Emocionalunclassified